Cauda Equina Conduction Time Determined by F-Waves in Normal Subjects and Patients With Neurogenic Intermittent Claudication Caused by Lumbar Spinal Stenosis. Issue 2 (March 2017) - Imajo, Yasuaki; Kanchiku, Tsukasa; Suzuki, Hidenori; Funaba, Masahiro; Nishida, Norihiro; Fujimoto, Kazuhiro; Taguchi, Toshihiko
Abstract : Purpose: Lumbar spinal stenosis typically presents with neurogenic intermittent claudication. The aim of this study was to investigate cauda equina conduction time (CECT) in patients with neurogenic intermittent claudication caused by lumbar spinal stenosis and its relationship with age and body height in normal subjects. Methods: The study included 172 normal subjects (group C) (mean age 44.1 ± 16.6 years; mean height 163.7 ± 8.9 cm). Forty-seven patients (group L) (mean age 71.3 ± 8.7 years; mean height 158.8 ± 11.2 cm) underwent surgery because of neurogenic intermittent claudication in cauda equina type of lumbar spinal stenosis. Motor-evoked potentials from the abductor hallucis were recorded. Magnetic stimulation was delivered at the S1 spinous process. Compound muscle action potentials (CMAPs) and F-waves were also recorded after supramaximal electric stimulation of tibial nerves. The peripheral motor conduction time (PMCT) was calculated from the latencies of CMAPs and F-waves as follows: (CMAPs + F-waves − 1)/2. The CECT was calculated by subtracting the onset latency of the motor-evoked potentials from PMCT. Results: The mean values for F-wave latencies, motor-evoked potential latencies, and CECT were 44.5 ± 3.3, 20.6 ± 1.8, and 3.4 ± 0.8 milliseconds, respectively. F-wave and motor-evoked potential latencies showed significant positive linear correlations with age and body height. However, no significant correlation was found between CECT and age ( P = 0.43) or body height ( P = 0.26). Mean CECT was 5.7 ± 1.5 in group L. There was a significant difference between groups C and L ( P < 0.05). Conclusions: The CECT value of normal subjects was 3.4 ± 0.8 milliseconds regardless of age and body height. We suggest that CECT may be a useful factor to consider when evaluating patients with neurogenic intermittent claudication.